IbM PENINGKATAN LIFE SKILL KELOMPOK TUKANG KAYU MELALUI PENDIDIKAN DAN PELATIHAN DI DESA KEMANTREN KECAMATAN JABUNG KABUPATEN MALANG - ', Parmo; Prianto, Kusnul; Seputro Y.P., Hariyono; Wahono, Arif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2017)
Unemployment may occur due to unavailability of employment or jobs available, but it is seasonal. Unemployment is seasonal, can occur in farming communities in rural areas that generally rely on natural factors or in community builders/construction workers who rely on the construction companies working on government projects. Often, between January to April each year, the community builders / construction workers were unemployed. This is due to the construction stage of the project is still at the stage of physical planning and construction work has not yet begun the stage. Kemantren village located in the eastern part of Malang actually save a lot of potential, both natural resource and the potential of human resources. However, according to records a lot of youth who drop out of school at the first level and intermediate. So most of the work as farmers, factory workers or builders/construction workers. Community service aims to improve the life skills carpenter through education and training so as to create self-sufficiency for individuals or groups of carpenters. Training provided in the form of an increase in skills in the manufacture of furniture and interior (table, chairs and a backdrop). Through this training are expected life skill of the groups of carpenters has sufficient capacity and skills in an effort to become entrepreneurs in the manufacture of furniture and or be recruited by the company because they already have the provision of skills in the manufacture of furniture and interiors.